PEMBENTUKAN NILAI RELIGIUS SEJAK PENDIDIKAN DASAR MELALUI MODEL DISKUSI KONTEKSTUAL DALAM PEMBELAJARAN FIKIH - Aristian Wahyudin; Itsna Rusydiana Itsna (LPPM IAD Probolinggo, 2026)
Fiqh learning in Madrasah Aliyah faces challenges in contextualizing instructional content to align with evolving social realities in the digital era, particularly in the teaching of Hajj jurisprudence, which is often delivered normatively. This study aims to examine the effectiveness of discussion-based learning in internalizing Hajj fiqh values and enhancing students’ contextual understanding. The research employs a qualitative descriptive approach with a phenomenological-evaluative design. Data were collected through semi-structured interviews, classroom observations, and documentation, with informants selected using purposive sampling. Data analysis followed the interactive model of Miles and Huberman, consisting of data condensation, data display, and conclusion drawing. The findings indicate that discussion-based learning promotes active student participation, strengthens critical thinking skills, and facilitates a more contextual and meaningful understanding of Hajj fiqh in relation to social, cultural, and regulatory dynamics in the digital era. Therefore, discussion-based learning can serve as an effective pedagogical strategy for improving fiqh instruction in Madrasah Aliyah